"Innocent" ventricular arrhythmia – can cardiovascular magnetic resonance augment diagnosis of structural heart disease?. (3rd October 2022) - Costa, C; Calvao, J; Amador, J; Proenca, T; Carvalho, M; Pinto, R; Cabrita, A; Marques, C; Oliveira, C; Santos, L; Pinho, A; Madureira, A J; et al.
Abstract: Background: Ventricular arrhythmias (VA) include a spectrum that ranges from premature ventricular beats (VPBs) to ventricular fibrillation (VF) and account for approximately 50% of all cardiovascular deaths. Echocardiography is commonly used to identify structural heart disease (SHD), the most frequent substrate of VA. Cardiovascular magnetic resonance (CMR) is recommended to complement echocardiography when image quality is suboptimal. Purpose: This study sought to determine whether CMR may identify SHD in patients (pts) with VA, who had normal baseline ECGs and whose echocardiogram with fair technical conditions, ruled out pathological findings. Methods: We included consecutive pts followed in arrythmia outpatient clinic of one clinical center from June 2014 to June 2021 for significant VA; this was categorized as >1, 000 but <10, 000 VPBs/24 h; ≥10, 000 VPBs/24 h; nonsustained ventricular tachycardia (NSVT), sustained VT, or a history of resuscitated cardiac arrest, and no pathological findings at echocardiography, requiring a clinically indicated CMR. Primary endpoint was CMR detection of SHD. Data were collected at the end of the study. Results: A total of 75 pts were included (no SHD: N=59; 45±15 years old; SHD: N=16, 53±15 years). All pts performed CMR, and Table 1 shows pts' baseline characteristics, VA diagnosis and CMR measurements. Definite SHD was diagnosed in 8 patients (11%): ischemic cardiopathy (three pts), myocarditis (1 pt), hypertrophic cardiomyopathy (1 pt), right ventricle arrhythmogenic disease (1 pt), non-compaction cardiomyopathy (1 pt); 1 patient presented higher myocardial T2 signal and was later diagnosed with sarcoidosis. Furthermore, abnormal findings not specific for a definite SHD diagnosis were found in other 8 pts (10%) who showed unspecific intra-myocardium enhancement. Discussion and conclusion: CMR imaging identified SHD in around 20% of patients with normal ECG and echocardiogram. Among patients with identified SHD, ischemic cardiopathy was the most common finding, differently from the largest study that showed myocarditis as the main diagnosis. This may be associated to higher age in the SHD group. In conclusion, CMR allowed diagnosis of clinically relevant SHD even when echocardiography excluded it. Funding Acknowledgement: Type of funding sources: None.